Meningkatkan Pemahaman Konsep Cahaya Melalui Penerapan Metode Praktikum Pada Siswa Kelas V SDI Paupanda 3 - Jamia Mohyeden (Ekspektasi: Jurnal Pendidikan Ekonomi, 2021)
The purpose of this study was to improve the learning outcomes of fifth grade students of SDI Paupanda 3 on the concept of light. This research is a classroom action research. The approach used in this study is a qualitative approach. Furthermore, the data collection techniques were observation or observation, tests and documentation. after applying the experimental method in learning science has increased. This is evidenced in the results of the observation of student learning tests in cycle I with a 52.20% completeness percentage increasing to 100% in cycle II. The increase in student learning outcomes from cycle I to cycle II was 47.8%.